Nuclear pore complex remodeling by p75(NTR) cleavage controls TGF-β signaling and astrocyte functions - Schachtrup, Christian (Nat Neurosci, 2015)
Astrocytes play critical roles in neuronal activity and inhibition of regeneration. Here we show that the cleaved p75 neurotrophin receptor (p75(NTR)) is a component of the nuclear pore complex (NPC) required for glial scar formation and reduced gamma oscillations in mice via regulation of TGF-β signaling. The cleaved p75(NTR) interacts with nucleoporins to promote Smad2 nucleocytoplasmic shuttling. Thus, NPC remodeling by regulated intramembrane cleavage of p75(NTR) controls astrocyte-neuronal communication in response to profibrotic factors.